Ordem de palavras em exclamativas com demonstrativos em Português Europeu - Joana Carvalho; Brito, Ana Maria (Revista da Associação Portuguesa de Linguística, 2016)
This paper focuses on the study of the syntactic position filled by the demonstrative determiner (este, esse, aquele) in nominal wh- exclamative sentences in European Portuguese (EP) like ‘Que menina esta!’. We draw on works on Spanish and Catalan (Castroviejo Miró 2006 a,b; Alonso Cortés 1999) and develop a hypothesis capable of explaining why the demonstrative in EP can occupy such a position, which apparently is a post-nominal one. We defend the hypothesis that in this type of exclamative the post-nominal position of the demonstrative is the result of an elliptical predicative clause. In order to understand the position of the demonstrative, we also analyse the structures of wh-exclamatives, of predicative clauses and of degree phrases.